Influence of lanthanum doping on the structural and optical properties of cerium tungstate nanocrystals. Issue 1 (1st March 2022) - Jose, Anjaly; H, Hitha; Kuriakose, Soumya; John, Mathew; varghese, Thomas
Abstract: In this study, the effect of lanthanum (La) doping on the structural and optical properties of cerium tungstate nanocrystals synthesized by the chemical precipitation method is investigated. The X-ray diffraction studies confirmed the crystalline phase formation and observed no phase change with doping. It is interesting to note that the crystallite size is decreased with La doping. The characteristic vibrational peaks of W-O bonds are confirmed from the FTIR and Raman spectroscopic studies and found no appreciable changes in the spectral positions with doping. The optical properties are studied using UV-Vis spectroscopy and photoluminescence spectroscopy. The characteristic broad blue PL emission from the tetrahedral tungstate group is observed for the pure and doped samples, and the appreciable variation in PL intensity can be associated with the formation of defects that occurred while doping.